Religion as a Determinant of Female Voting Behaviour in District Karak: A Case Study of The 2018 General Election - Rifat Nazir; Ashfaq U. Rehman; Muneeb U. Rehman, (ASIAN Journal of International Peace & Security (AJIPS), 2024)
This study investigates the role of ‘religion’ as a determinant influencing female voting behaviour and analyses its impact on the 2018 General Elections in District Karak. To understand voting behaviour, the researcher has connected this determinant with voting behaviour theory, namely, the theory of religion. As regards the application of the theory, it is argued that the theory is applicable (63.65%) in the electoral politics of District Karak. This study is based on published and unpublished data. This article answers the question i.e., is religion the determinant of female voting behaviour in the 2018 General Election in NA-34 District Karak? Moreover, what are the impacts of female voting behaviour on the 2018 General Elections in NA-34 District Karak? Primary and secondary data have been collected for this research work. A quantitative research approach has been applied. The population was the registered female voters of District Karak. Through the Yamoni formula, data is collected from 400 respondents. A stratified sampling technique is used to collect data from registered female voters. There are three Tehsil: Banda Daud Shah, Takht-e-Nasrati and Karak. Therefore, the study used a proportional allocation method of sampling, i.e. n1=N1/Ni x ni, to select the respondents according to the sample size from each tehsil. Data has been arranged in Tables, which are further analyzed.